2007
DOI: 10.1016/j.neuroimage.2007.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Common regions of dorsal anterior cingulate and prefrontal–parietal cortices provide attentional control of distracters varying in emotionality and visibility

Abstract: Top-down attentional control is necessary to ensure successful task performance in the presence of distracters. Lateral prefrontal cortex, parietal cortex and anterior cingulate cortex have been previously implicated in top-down attentional control. However, it is unclear whether these regions are engaged independent of distracter type or whether, as has been suggested for anterior cingulate cortex, different regions provide attentional control over emotional versus other forms of salient distracter. In the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 82 publications
4
28
0
5
Order By: Relevance
“…47 Moreover, recent findings indicate that activity in left DLPFC, right posterior parietal cortex and right dorsal ACG is greater as a function of the emotional salience and visibility of emotional information during a lexical decision-making task. 48 Findings from the above studies, therefore, indicate that bilateral DLPFC, right dorsal ACG and right parietal cortex are important in supporting voluntary attentional control subprocesses. Again, it is possible that modulation of subcortical limbic regional activity by these lateral and dorsal regions of the PFC during voluntary control of attention away from emotional material may occur indirectly via the OFC.…”
Section: Voluntary Subprocessesmentioning
confidence: 87%
“…47 Moreover, recent findings indicate that activity in left DLPFC, right posterior parietal cortex and right dorsal ACG is greater as a function of the emotional salience and visibility of emotional information during a lexical decision-making task. 48 Findings from the above studies, therefore, indicate that bilateral DLPFC, right dorsal ACG and right parietal cortex are important in supporting voluntary attentional control subprocesses. Again, it is possible that modulation of subcortical limbic regional activity by these lateral and dorsal regions of the PFC during voluntary control of attention away from emotional material may occur indirectly via the OFC.…”
Section: Voluntary Subprocessesmentioning
confidence: 87%
“…Moreover, the rsFCs between the SFG and the ACC and MCC have been reported (Yu et al, 2011). The anatomical and functional connections between the SFGam and the anterior MCC suggest that the SFGam is involved in cognitive control because the anterior part of the MCC (also named dorsal ACC in many studies) has always been related to cognitive control, such as conflict monitoring (Sohn et al, 2007;Ursu et al, 2009), error detection (Gehring and Fencsik, 2001;Pourtois et al, 2010), response selection (Awh and Gehring, 1999;Paus, 2001), and attention control (Crottaz-Herbette and Menon, 2006;Luo et al, 2007). Additionally, the SFGam is anatomically connected with the ACC which is a core node of the DMN and functionally correlated with the DMN, which suggests that the SFGam is a node of the DMN and is involved in self-referential processing (Northoff et al, 2006).…”
Section: Connectivity Profiles Of the Sfgammentioning
confidence: 99%
“…Once such a stimulus is detected, the right AI initiates appropriate transient control signals to engage the dACC and prefrontal cortices that mediate attention, working memory and other higher order cognitive processes while disengaging the DMN (Menon and Uddin, 2010). The dACC has been reported to be involved in a variety of executive functions, such as attention control (Crottaz-Herbette and Menon, 2006;Luo et al, 2007;Smith and Jonides, 1999), conflict monitoring (Botvinick et al, 2004;Carter and van Veen, 2007;Carter et al, 1998), error monitoring and detection (Gehring and Fencsik, 2001;Gehring and Knight, 2000;Lorist et al, 2005;Pourtois et al, 2010), and response selection (Awh and Gehring, 1999;Paus, 2001). We found that C-carriers simultaneously exhibited a decrease in GMV and an increase in synchronization in the dACC bilaterally compared to TT individuals, and we also found increased synchronization in the right AI and the bilateral caudate nucleus of the ECN.…”
Section: Kibra and Ecnmentioning
confidence: 99%